Nepal Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2016)
This report provides an assessment of accounting, financial reporting and auditing requirements and practices in Nepal. The report uses international financial reporting standards and international standards on auditing as benchmarks and draws on international experience and good practices in the field of accounting and audit to assess the quality of financial reporting and make policy recommendations. The reports on the observance of standards and codes (ROSC) accounting and auditing addresses two strategic objectives in the Country Partnership Strategy FY14-FY18 (poverty reduction and shared prosperity). The report aims to support the Government of Nepal in preparing a country action plan aimed at further enhancing the quality of corporate financial reporting to facilitate improvement of business climate, attract foreign direct investment, and foster business development. The policy recommendations also target small and medium enterprises that form the backbone of Nepal's economy.